How Cool is That? The Effects of Menthol Mouth Rinsing on Exercise Capacity and Performance: A Systematic Review and Meta-analysis - Erica H. Gavel; Gabriel Barreto; Kierstyn V. Hawke; Trent Stellingwerff; Lewis J. James; Bryan Saunders; Heather M. Logan-Sprenger (SpringerOpen, 2024)
Abstract Background Menthol (MEN) mouth rinsing (MR) has gained considerable interest in the athletic population for exercise performance; however, the overall magnitude of effect is unknown. Objective The aim of this systematic review and meta-analysis was to determine the efficacy of menthol MEN MR and the impact it has on exercise capacity and performance. Methods Three databases were searched with articles screened according to the inclusion/exclusion criteria. Three-level meta-analyses were used to investigate the overall efficacy of MEN MR and the impact it has on exercise capacity and performance. Meta-regressions were then performed with 1) mean VO2peak, 2) MEN swilling duration; 3) the MEN concentration of MR solution, 4) the number of executed swills throughout a single experiment, 5) the use of flavoured sweetened, non-caloric, or non-flavoured neutral solutions as controls, 6) mean environmental temperature at the time of exercise tests, and 7) exercise type as fixed factors to evaluate their influence on the effects of MEN MR. Results Ten MEN MR studies included sufficient information pertaining to MEN MR and exercise performance and capacity. MR with MEN resulted in no significant change in capacity and performance (SMD = 0.12; 95% CI − 0.08, 0.31; p = 0.23, n = 1, tau21 < 0.0001, tau22 =  < 0.0001, I 2 = 0%). No significant influence was detected in meta-regressions for VO2peak, (estimate: 0.03; df = 8; 95% CI − 0.03, 0.09; p = 0.27), swilling duration (5 vs. 10 s: 0.00; df = 16; 95% CI − 0.41, 0.41; p = 1.0), MEN concentration (low [0.01%] vs. high [0.1%]: − 0.08; df = 15; 95% CI − 0.49, 0.32; p = 0.67), number of swills (estimate: 0.02; df = 13; 95% CI − 0.05, 0.09; p = 0.56), the use of flavoured sweetener or non-caloric as control (non-flavoured vs. flavoured: 0.12; df = 16; 95% CI − 0.30, 0.55; p = 0.55) or mean room temperature during exercise tests (estimate: 0.01; df = 16; 95% CI − 0.02, 0.04; p = 0.62). Conclusion MEN MR did not significantly improve overall exercise capacity and performance, though those involved in endurance exercise may see benefits.